CU-63 NMR OF HG-1223 BETWEEN 100K AND 300K - Michalak, R; Dupree, R; Edwards, P; Marezio, M; Capponi, J (1994)
The temperature dependence of the 63Cu - NMR shift has been investigated between 100K and 300K for Hg-1223. The temperature dependence of the outer plane copper site is found to be typical for that observed in overdoped systems. © 1994.